2016
DOI: 10.1590/s0100-204x2016001000001
|View full text |Cite
|
Sign up to set email alerts
|

Indutores de resistência abióticos no controle da fusariose do abacaxi

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de indutores de resistência abióticos no controle da fusariose (Fusarium guttiforme) do abacaxizeiro na fase pré-colheita, em área de ocorrência natural da doença, e verificar se promoveram alterações físico-químicas e bioquímicas nos frutos. Os produtos testados foram fosfito de potássio, fosfito de cálcio, fosfito de cobre, Agro-Mos, silicato de cálcio, Biopirol e Bion pulverizados em campo, nas dosagens recomendadas pelos fabricantes. Fosfito de potássi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…The result found in the present study confirms the existing literature data. Melo et al (2016) obtained reduction in the Fusarium guttiforme incidence in pineapples with application of copper phosphite. Dantas et al (2018) observed inhibition in the development of Alternaria sp., C. gloeosporioides, Fusarium sp., Geotrichum sp.…”
Section: Treatmentsmentioning
confidence: 92%
See 2 more Smart Citations
“…The result found in the present study confirms the existing literature data. Melo et al (2016) obtained reduction in the Fusarium guttiforme incidence in pineapples with application of copper phosphite. Dantas et al (2018) observed inhibition in the development of Alternaria sp., C. gloeosporioides, Fusarium sp., Geotrichum sp.…”
Section: Treatmentsmentioning
confidence: 92%
“…and Lasiodiploidia theobromae fungi using the same copper phosphite formulation. There is no evidence that plants benefit from phosphite as source of phosphorus; however, the elements that accompany this molecule in phosphite-based products such as zinc (zinc phosphite) can act in nutrition, providing this element to plants (DALIO et al, 2012) and having direct action on the pathogen (SILVA et al, 2016). In addition, micronutrients act as cofactors for enzymes involved in the synthesis of phenolic compounds (SILVA et al, 2008).…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread and persistent nature of spp. may be due to its ability to maintain and multiply in a wide variety of complex carbohydrates and proteins, thus resisting adverse climates and high levels of toxic substances such as many antibiotics and seems to incorporate some of the most difficult members of the genus According to Resende et al [34] and Melo et al [35], Cu, Zn and K compounds are used for the control of microorganisms. They can have a direct effect on the pathogen (fungicidal or fungistatic effect) or activate the natural defense of plants, resulting in induced resistance [36,37].…”
Section: F Solani F Sp Piperis On Cuso 4 Znso 4 (A) and Kcl (B) mentioning
confidence: 99%
“…In addition, the enzymatic changes can be related to physiological aspects in combination with the induction of the plant's resistance to diseases. Several reports have demonstrated a relationship between induced systemic resistance and enzymes such as peroxidase, polyphenol oxidase, phenylalanine ammonia lyase, β-1,3-glucanase and chitinase (Van Loon, Bakker, & Pieterse, 1998;Chithrashree et al, 2011;Nascimento & Barrigossi, 2014;Melo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%